Prospects for the Improvement of Criminal Liability for Hostage-Taking Offenses - Annakulov, Azamat (Indonesian Journal Publisher, 2025)
This article analyzes the problems and prospects for improving criminal liability for the offense of taking a person hostage. From the perspective of public security, the author evaluates the high degree of social danger posed by this crime and examines the deficiencies in the current legal response. A comparative legal analysis of national and international legislation is conducted to identify gaps and inconsistencies in the legal regulation of hostage-taking. Particular attention is given to the need for harmonizing Uzbekistan’s criminal code with international legal standards. The article also outlines proposals for enhancing pre-crime prevention measures and improving the efficiency of investigation and prosecution processes. Drawing on the experiences of foreign countries, the study substantiates the necessity of introducing targeted amendments to domestic legislation to ensure timely legal responses and greater protection of public safety. The author argues that a multidisciplinary and proactive legal approach, supported by interagency cooperation and modern investigative methods, is essential for effectively deterring and addressing hostage-taking offenses in contemporary criminal justice practice.